Error detection and filtering of incompressible flow simulations for aeroacoustic predictions of human voice - Schoder, Stefan; Kraxberger, Florian; Falk, Sebastian; Wurzinger, Andreas; Roppert, Klaus; Kniesburges, Stefan; Döllinger, Michael; Kaltenbacher, Manfred (Journal of the Acoustical Society of America, 2022)
The presented filtering technique is proposed to detect errors and correct outliers inside the acoustic sources, respectively, the first time derivative of the incompressible pressure obtained from large eddy simulations with prescribed vocal fold motion using overlay mesh methods. Regarding the perturbed convective wave equation, the time derivative of the incompressible pressure is the primary sound source in the human phonation process. However, the incompressible pressure can be erroneous and have outliers when fulfilling the divergence-free constraint of the velocity field. This error is primarily occurring for non-conserving prescribed vocal fold motions. Therefore, the method based on a continuous stationary random process was designed to detect rare events in the time derivative of the pressure. The detected events are then localized and treated by a defined window function to increase their probability. As a consequence, the data quality of the non-linearly filtered data is enhanced significantly. Furthermore, the proposed method can also be used to assess convergence of the aeroacoustic source terms, and detect regions and time intervals, which show a non-converging behavior by an impulse-like structure.
CRIS-Team Scopus Importer:2022-09-30